Grundtvig i dag - Michelsen, William (Grundtvig-Studier, 1985)
Grundtvig Today The Land of the Living, 1984. Edited by Flemming Ettrup and Johannes H. Christensen. Reviewed by William Michelsen The main content of this book is a series of lectures given at Skovshoved Church in Copenhagen in 1983. It is published by the Danish Library Society and contains important contributions to the current debate on Grundtvig. This is particularly true of the three lectures by the three professors, Christian Thodberg, Leif Grane and Aage Henriksen. Thodberg discovers the background for the poem The Land of the Living in Grundtvig’s sermons and biblical poetry. Leif Grane applies a present-day theological point of view to defend Grundtvig’s standpoint in The Church’s Retort (Kirkens Gienm.le), while Aage Henriksen maintains that Grundtvig himself cannot be bounded by the world of ideas represented by the Church. He is answered by Ejvind Larsen, and adds a “preliminary” reply himself. The reviewer points out that Aage Henriksen’s lecture was also given in a Danish church, and that the Danish Church is more open than most, thanks not least to Grundtvig’s great contribution to Church freedom from 1832 onwards. His greatness lies in the fact that at one and the same time he maintained the sharp distinction between Christianity and non-Christianity and the right for people of a different persuasion to speak with the same freedom as he himself and every other Christian.